The Concept of a Sakinah Family from the Perspective of Islamic Religious Education: A Juridical-Normative Analysis of Contemporary Islamic Family Law in Indonesia - Riza Ruchmana; Ikhwanul Hakim (International Journal of Sociology of Religion, 2026)
This study aims to analyze the concept of a sakinah family from the perspective of Islamic Religious Education and to examine its relevance to contemporary Islamic family law in Indonesia. The method used is library research with a juridical-normative approach through the analysis of Islamic legal sources, Islamic Religious Education literature, and family law regulations in Indonesia. The results of the study indicate that a sakinah family is an ideal concept encompassing values of tranquility, affection, and mercy, derived from the teachings of the Qur’an and Hadith. From the perspective of Islamic Religious Education, a sakinah family is formed through the internalization of moral values, spirituality, and responsibility. Meanwhile, in contemporary Islamic family law in Indonesia, these values have been accommodated in the Marriage Law and the Compilation of Islamic Law, although there remains a gap between legal norms and social realities. This study also finds that the integration of Islamic Religious Education and family law is crucial in realizing a holistic sakinah family. Therefore, synergy among education, law, and public awareness is needed to strengthen family resilience in the modern era.